Rome Regulations commentary - Calliess, Gralf-Peter; Renner, Moritz, 1981- (Wolters Kluwer, 2020)
With the so-called Rome I, II and III Regulations the Member States of the European Union are bound to a common set of rules for the choice of law in international private law disputes. They apply to both contractual and non-contractual disputes, their reach even extends to the application of non-Member State law. This poses great challenges to Courts and practitioners in every EU Member State, as there is only little case-law and doctrinal literature on the new rules, the uniform application of which will be overseen by the European Court of Justice. The Commentary answers to these challenges. It is an indispensable companion for both academics and legal professionals seeking their way through the Regulations. Renowned conflict of laws scholars comment every provision of the Regulations in a systematic, thorough and comprehensive manner, making them accessible to a broad international legal audience. Mirroring the German tradition of scholarly commentaries on Parliamentary Acts, the authors are selected from the distinguished group of relatively young German private international law scholars, whose exceptionally high qualifications are represented by their passing through the German Habilitation-system (second book requirement) as well as their proven ability to publish in the English language"--Provided by publisher.